The Physicochemical Properties and Consumer Acceptance of Ricegrass Beverage Ready for Consumption - Uprawanna, Utsaphong; Norchai, Phitchakorn; Thongrote, Chananbhorn (Journal of Food Health and Bioenvironmental Science, 2023)
Juice extracted from riceberry grass has exhibited higher phenol and antioxidant activity. The objective of this research was to enhance the value of ricegrass and to develop a product that small community enterprises can follow through the entire production process. This study was designed to examine the physicochemical, microbiological properties and sensory evaluation of ricegrass juice and ricegrass juice mixed with soybeans and navy beans (SN) milk. Rice leaves were extracted with room temperature water at ratios of 10:1, 2:1, 1:1, 1:5 and 1:10 (w/v) and with hot water at ratios of 2:1 and 1 :1 (w/v). The results revealed that ricegrass leaves extracted with room temperature water at a ratio of 1 :5 (w/v) had a higher yield, total phenol and antioxidant activity. The sensory evaluation found that 30% of ricegrass juice that was mixed with 1 0 % SN milk had the highest acceptance score on all attributes. Pasteurized products stored at 4°C for 8 days were close near to the Thai community product standard (TCPS 529/2547), but total phenol and antioxidant activity decreased during storage (p ≤ 0.05). Furthermore, ricegrass juice mixed with SN milk product is a functional drink which has plenty of phenol, antioxidant and nutrition.